Effect of hydrogen plasma treatment on secondary electron emission properties of polycrystalline diamond films. (February 2020) - Wei, Kongting; Li, Jie; Liu, Biye; Wu, Rongrong; Wei, Qiang; Wu, Shengli; Hu, Wenbo; Wang, Hongxing
Abstract: The polycrystalline diamond films were prepared by microwave plasma chemical vapor deposition (MPCVD), and the prepared diamond films were treated with hydrogen plasma for different times. The secondary electron emission (SEE) performance of these films were studied. The film treated with plasma for 10 min has the highest SEE yield. It was found that when the films are exposed to the hydrogen plasma, the film surfaces are etched with the hydrogen plasma and the surface content of C–H components are increased with the exposure time, conversely, the oxygen content of the surfaces are gradually reduced, which leads to the higher SEE yield. When the film is continuously irradiated by the incident electron beam, the SEE yield will decrease with time, this is because the electron beam bombardment destroys the hydrogen-termination and decreases the film's surface negative electron affinity (NEA). Highlights: An increase in the C-H content and a decrease in the oxygen content of the surface result in a higher SEE yield. The SEE yield will decrease because the electron bombardment destroys the hydrogen-terminated surface. High SEE yield can be obtained by treating the diamond film with hydrogen plasma for a reasonable time.